(untitled) (Revista Educação, Artes e Inclusão, 2023)
The present work analyzes thirteen scientific articles, published in the journal Educação, Artes e Inclusão (Education, Arts and Inclusion, in english) between the years 2010 and 2020, contemplating the interdisciplinarities in school and non-school spaces, the pluralities in the teaching of Visual Arts and teacher training, for the processes of inclusive education. Therefore, the following specific objectives were outlined: Understanding of theoretical aspects of the teaching of visual arts in inclusion processes; contextualize the Educação, Artes e Inclusão journal between the years 2010 and 2020, with a fine selection for this study and refine references that point to the skills needed in the teaching practice. The exploratory and qualitative research proposed artistic and analytical interventions, constituted from the reading, reflection and perception of articles presented here briefly. Likewise, it sought to reflect on what training skills of teaching is presented in this process, therefore understanding that the equipment necessary for its performance is constituted of an expansion of repertoires, to be offered to its students, with the purpose of bringing the heterogeneities of the subjects existing in these spaces.